Profile of phenolic compounds in jabuticaba (Myrciaria sp.) a potential functional ingredient. Issue 14 (15th July 2022) - dos Santos, Mônica Cristine Pereira; Cavalcanti, Elisa d'Avila Costa; Santos, Millena C. Barros; Seljan, Mariana Pulmar; Cameron, Luiz Claudio; Ferreira, Mariana Simões Larraz; Gonçalves, Édira Castello Branco de Andrade
Abstract: Phenolic compounds have attracted a lot of attention due to their benefits to human health. Jabuticaba ( Myrciaria sp. ) fruit has been described as an excellent source of these compounds, while Jabuticaba leaf, considered as plant residue, has shown functional effects. The present study aimed to characterize the phenolic profile in two different leaves extracts (hydroalcoholic ethanol and butanol) of Myrciaria sp. by UPLC-ESI-QTOF-MS E . A total of 40 phenolic compounds were tentatively identified. Jabuticaba leaf extracts presented a rich and diversified composition of phenolic compounds, especially flavonoids, being ellagic acid, quercetin 3-O-glucoside, gallocatechin, and epigallocatechin the most abundant in butanol extracts. Very distinct phenolic profiles were obtained depending on the the solvent indicating that specific preparations can be obtained from the jabuticaba leaf depending on the desired application. This work emphasized the potential of this residue vegetable to be used as a functional ingredient. Graphical abstract: UF0001